Analysis of Public Services in Creating Taxpayer Identifica-tion Number (NPWP) at The Dumai City Primary Tax Ser-vice Office (KPP) - Dede Mirza; Rudi Hartasetiadi; Ernita Puspa Dewi; Ajeng Putri Wiharni (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Public service delivery in taxation is a vital function of government in fulfilling citizens' administrative rights, particularly through the issuance of the Taxpayer Identification Number (NPWP). The quality of this service directly influences taxpayer satisfaction, understanding, and trust in tax institutions. This study aims to analyze the quality of public service in NPWP issuance at the Primary Tax Office (KPP Pratama) of Dumai City and to identify supporting and inhibiting factors affecting service implementation. This research employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews with tax officers and taxpayers, and documentation studies. Data analysis was conducted using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The assessment of service quality was based on the SERVQUAL framework developed by Zeithaml and Parasuraman, encompassing five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results show that NPWP issuance services at KPP Pratama Dumai City are generally well implemented. Adequate facilities, adherence to standard operating procedures, responsive officers, data security assurance, and courteous service attitudes support service quality. However, challenges remain, particularly related to limited waiting room capacity during peak periods, varying levels of taxpayer understanding, and the need for clearer procedural information. Continuous improvement in communication, service management, and capacity planning is required to enhance public service quality.